Comparison of previously injured body regions in elite freestyle and Greco-Roman wrestlers - Çebi, M.; Imamoglu, O.; Yamak, B.; Eliöz, M.; Yildiz, M. (Physikalische Medizin - Rehabilitationsmedizin - Kurortmedizin, 2022)
The aim of this study was to compare the injured body regions that elite Freestyle and Greco-Roman wrestlers suffered from and to determine the importance of injuries. 41 Freestyle and 51 Greco-Roman wrestlers, who were practicing in Turkish National Wrestling Team camps, participated in this study. `Chi Square` and student t tests were used in statistical analyses. When examined injury status and body regions distribution between Freestyle and Greco-Roman wrestlers, significant difference was found in head and trunk injuries according to wrestling styles (p<0.05). No difference was found in upper/lower extremities and lesion/scrape and friction burns status of the wrestlers according to wrestling style (p>0.05). There was significant difference in trunk and upper extremity injuries with respect to weight category (p<0.05 and p<0.001). Significant difference was also found in nose injuries according to wrestling styles (p<0.05). When examined wrestling style and upper extremity injuries according to the number of injuries, there was found significant difference between two styles in muscle injuries, finger and wrist injuries (p<0.05). The difference between toe injuries in respect to the wrestling style was statistically significant (p<0.05). Results: Greco-Roman wrestlers experienced more injuries in trunk, head and nose compared to Freestyle wrestlers. Trunk, lower and upper extremity injuries varied depending on weight categories. Neck, back, lumbar and chest injuries were more common in Greco-Roman wrestlers. Freestyle wrestlers were more vulnerable to muscle injuries while Greco-Roman wrestlers were more vulnerable to finger and wrist injuries. It is recommended to improve some abilities excellently such as aerobic power, strength, balance and neuro-motor coordination in wrestling. Techniques should be taught well to the wrestlers, most risky extremities for injury have to be applied extra training and these extremities should be protected from injuries by several tapes, bandages or gears during exercise. Freestyle wrestlers ought to be more careful in diving move. Using ear protector in addition to preventive measures can be recommended during training in order to prevent temporal bone fractures and swellings.